PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS III SEKOLAH DASAR: PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS III SEKOLAH DASAR - tri wera agrita (Jurnal Tunas Pendidikan, 2021)
The problem in this study is the low learning outcomes of grade III students of SD Negeri 201/II Baru Telentam from 18 students by 31% who have compeleted, the aim is improve student learning outcomes in mathematics in grade III through a problem based learning model. The from of this research (CAR) for two cycles, each cycle consisting of four stages namely planning, implementing, observing, reflecting. Data collection using observation, interviews, documentation, and test. The results showed that the mathematics learning outcomes of studentsi in the first cycle contained 55% of students who completed with an average grade of 79.2. it shows there has been an increase in percentage from cycle II by 22%. Based on the results of this study, it can be concluded that the application of problem based learning model can improve mathematics learning outcome of fourth grade students of elementary 201/II Baru Telentam, Kecamatan Tanah Tumbuh, Kabupaten Bungo.